Pengembangan Aplikasi Presensi dan Pemantauan Penerapan Protokol Kesehatan dalam Pencegahan Penyebaran COVID-19 pada Platform Android - Eka Iqbal Virgiawan; Agi Putra Kharisma; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The amount of mobility and interaction during work activities makes companies need to anticipate the transmission of COVID-19 in the work environment. In anticipating the transmission, it is necessary to monitor workers in implementing health protocols while in the workplace. To help with this, an Android-based mobile application will be developed that can minimize physical contact and inform if there is a violation of health protocols. This application will use the geofencing method by utilizing the Global Positioning System (GPS) sensor. Application development will use the Waterfall method because the requirements have been defined from the start and there are no changes. The application was developed using the Model View ViewModel (MVVM) architecture with the Kotlin programming language and XML markup language. There are 3 tests that will be carried out, namely testing the use of energy, functional, and usability. Tests of energy use showed the majority of the results were mild. However, in functional testing, it is known that there is 1 functional requirement that currently cannot be realized because it is very dependent on the level of accuracy and precision of the GPS sensor. The usability test for the person in charge gets a 100% success rate with a System Usability Scale (SUS) score of 83 which can be categorized in the acceptable category with grade A. Meanwhile, workers get a 100% success rate with a SUS score of 70 which can be categorized in the marginal category with grade C.